14‐4L: Late‐News Paper: Self‐Pattern Process of InZnO Thin‐Film Transistors using Photosensitive Precursors. Issue 1 (May 2017) - Kim, Hee Jun; Kim, Yeong-gyu; Park, Sung Pyo; Kim, Dongwoo; Kim, Na-eun; Choi, Jong Sun; Kim, Hyun Jae
Abstract : We demonstrated self‐patternable InZnO (IZO) thin‐film transistors (TFTs) using photosensitive precursors. UV‐irradiated films became cross‐linked and solution‐processed IZO films were patterned successfully. Compared to self‐patterned IZO TFTs using photosensitive activators, precursor‐based self‐patterned IZO TFTs have better electrical characteristics and stability due to having less organic residues.